Comparison Between Ultrasonography and Galactography in Detecting Lesions in Patients With Pathologic Nipple Discharge. Issue 1 (March 2019) - Jung, Hyun Kyung; Park, Young Mi; Baek, Hye Jin; Choo, Hye Jung; Kim, Eun-Kyung; Kim, Dong Wook; Lee, Sun Joo; Lee, Jin Hwa
Abstract : Purpose: This study aimed to compare the diagnostic performance of breast ultrasonography (US) with that of galactography in the detection of lesions in patients with pathologic nipple discharge. Methods: We included 46 cases from 39 patients (all women; mean age, 44.0 years; range, 22–68 years) who had pathologic nipple discharge and underwent US and galactography between March 2004 and December 2012. Two radiologists retrospectively reviewed and compared the detectability of lesions on US and galactography images. A receiver operating characteristic (ROC) curve analysis was performed to evaluate the diagnostic performance of US and galactography, and the area under the curve was compared between the 2 imaging modalities. Results: A total of 35 cases were pathologically diagnosed. Out of 11 cases that completed a follow-up, none developed malignancies during the follow-up period (mean: 63.5 months; range: 34.8–125.7 months). The sensitivity, specificity, and positive and negative predictive values of US with respect to detectability of lesions were 75%, 42.9%, 11.1%, and 94.7%, respectively, and those of galactography were 100%, 38.1%, 13.3%, and 100%, respectively. Conclusions: Galactography is more sensitive than US in the detection of lesions in patients with pathologic nipple discharge.